Hubungan antara Terpaan Iklan (Advertising Exposure) dan Kualitas Produk Dengan Keputusan Menggunakan Telkom Speedy di Wilayah Kota Semarang - Sinta Petri Lestari (Universitas Pandanaran, 2018)
Abstract: Telecommunications Company is a company engaged in the field of telecommunications services so that customer satisfaction is the main factor that should be improved for the sake of survival. If it is not addressed then it is likely consumers will not be back to buy the product will even switch keperusahaan another. Service quality and corporate image merupaka other factors which must be maintained and enhanced. The purpose of this study was to analyze the magnitude of the influence of perceptions of quality products and quality service to customer satisfaction. The data in this study were obtained from customers speedy product at PT. Telekomunikasi Indonesia. Results and the theoretical implications of this research is that this study supports previous research that says that the quality of products, quality service and prices affect consumer satisfaction. Speedy technology use ADSL, ISP infrastructure, VoIP, Bandwidth. Provide speedy speed connection to the internet is faster than using a regular dial- up service. Have a speedy connection speed downloading (downstream) to maxima of 1 Mbps and upload speeds (upstream) reach a maximum of 128 Kbps. Dial-up service only provides a maximum speed of 56 Kbps.Keyword: Advertising Exposure, Quality Products, Consumer Decision